APPLICATION OF IFRS WITH DISCLOSURE OF FIXED ASSETS IN THE COMPANY'S FINANCIAL STATEMENTS - Rizky, Nonon Dherian; Asad Sutrisna, Wawan (Accounting Research Journal, 2023)
Abstract. The aim of this research is to analyze the implementation ofIFRS and its relationship with the comparison of disclosure of fixedassets or now called PPE (Property, Plant, and Equipment) in financialreports. The variable used in this research is the application of IFRSwhich focuses on the comparison of PPE disclosures. This research isbased on previous research conducted by Vergauwe and Gaeremynck(2013). The sample for this research is manufacturing companies listedon the Indonesia Stock Exchange (BEI) in 2019-2022. Data wascollected using a purposive sampling method, observations wereanalyzed. Hypothesis testing in this research uses regression analysisBased on the results of the regression test, the application of IFRS doesnot have a significant effect on the disclosure of fixed assets in financialstatements.Keywords: Implementation of IFRS, Disclosure of Fixed Assets,Financial Reports